2023
DOI: 10.2196/44195
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Maslach Burnout Inventory Among Public Health Care Professionals: Scoping Review

Abstract: Background Work can be considered a source of living, well-being, and socioeconomic development. When the work environment negatively influences individuals, it may trigger emotional disturbances, behavioral problems, chronic stress conditions, and illnesses such as burnout syndrome (BS). Recently, studies on BS have increased and placed a special focus on health care professionals. The prevalence of BS among health professionals is associated with their chronic exposure to human hardship and long … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 93 publications
(196 reference statements)
2
6
0
Order By: Relevance
“…Another impact our fellowship demonstrated was improvement in fellows’ emotional exhaustion and depersonalization, but not in stress, work engagement, or personal achievement. At baseline, the scores for our fellows were similar compared to other published reports on clinician burnout [ 11 , 12 ]. Given that burnout is driven by systems-level factors rather than individual factors, the high rates of burnout and limited improvement in fellows’ wellness indicators even after training in individual and organizational wellness further proves the importance of training leaders in primary care transformation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Another impact our fellowship demonstrated was improvement in fellows’ emotional exhaustion and depersonalization, but not in stress, work engagement, or personal achievement. At baseline, the scores for our fellows were similar compared to other published reports on clinician burnout [ 11 , 12 ]. Given that burnout is driven by systems-level factors rather than individual factors, the high rates of burnout and limited improvement in fellows’ wellness indicators even after training in individual and organizational wellness further proves the importance of training leaders in primary care transformation.…”
Section: Discussionsupporting
confidence: 82%
“…More recently the Quintuple Aim in health care has introduced health equity as its own pillar to improve both the care setting for health care professionals and the care and health of underrepresented and minoritized patient populations, further emphasizing the need for advocacy and leadership in primary care [ 10 ]. Additionally, given that close to 50% of clinicians in direct patient care experience burnout syndrome, and given an increasing aging population and complexity of patients, transformation of primary care is more critical than ever to meet the needs of patients and clinicians [ 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey employing the validated and widely used Maslach Burnout Inventory demonstrated that over 75% of emergency medicine resident physicians experience burnout—an occupational phenomenon defined by the World Health Organization as a syndrome “resulting from chronic workplace stress that has not been successfully managed” [ 1 , 2 , 3 , 4 ]. The etiology of burnout is multifactorial, but it is inherently both an occupational patient safety and physician wellness issue.…”
Section: Introductionmentioning
confidence: 99%
“…Health care professionals receive intensive hands-on education and training so they may serve as resilient healers. Yet, with high workloads and multitasking demands, physicians can become vulnerable to workplace stress while making critical life-altering decisions for patients [ 1 , 2 ]. Evidence shows high rates of physician burnout (“workplace stress that has not been successfully managed,” International Classification of Diseases , World Health Organization), currently estimated at 44%, which is much higher than burnout in other professions [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Relative to a no-contact or business-as-usual control group, we evaluated the primary outcomes of change in mindfulness and self-compassion and monitored sessions of training engagement. While we additionally measured burnout, we did not expect this outcome to change with individual-focused training because it has been shown that organization-directed workplace interventions are more effective at addressing burnout [ 1 , 25 ] and burnout was also observed to be low in our sample. Thus, our main goal in this study was to examine whether mindfulness and compassion can be enhanced by brief digitally delivered practice sessions for health care professionals.…”
Section: Introductionmentioning
confidence: 99%